A new adhesive bone conduction hearing system effectively treats conductive hearing loss in children. (July 2019) - Neumann, Katrin; Thomas, Jan Peter; Voelter, Christiane; Dazert, Stefan
Abstract: Objectives: Bone conduction hearing devices integrated in softbands (BCDSs) are frequently not well accepted by children with conductive hearing loss due to pressure on the head, sweating, or cosmetic stigma. A non-surgical hearing system (ADHEAR) uses a new bone conduction concept consisting of an audio processor connected to an adhesive adapter fixed behind the ear. This study is the first to evaluate the audiological and clinical outcome of this novel system, comparing it with conventional BCDSs in a short- and mid-term follow-up in children under 10 years of age. Methods: The ADHEAR was compared to a BCDS in 10 children with conductive hearing loss (age: 0.7–9.7 years). Aided and unaided pure tone/behavioral observational audiometry and, if applicable, speech audiometry in quiet and noise were performed initially with both devices and after 8 weeks with the ADHEAR alone. The subjective hearing gain and usage of the new hearing system, as well as patients' and parents' satisfaction were assessed using questionnaires. Results: The functional gain with the ADHEAR averaged over 0.5, 1, 2, and 4 kHz exceeded that of the conventional BCDS (35.6 dB ± 15.1 vs. 29.9 dB ± 14.6, p = .001, n = 9 ears). Speech perception in quiet and noise ( n = 8) improved in the aided situation similarly for both hearing devices. The parents of 8 of 10 children evaluated the ADHEAR system as being useful. Minor wearing problems occurred occasionally. Eight children continued using the ADHEAR after the study, one received an active middle ear implant and one continued to use a BCDS. Conclusion: The ADHEAR system is a promising solution for children with conductive hearing loss or chronically draining ears.